David in the fourth gospel : the Johannine reception of the Psalms - Daly-Denton, Margaret. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2000)
This volume deals with the reception of the psalms in the New Testament, taking as an example the Fourth Gospel, a work profoundly shaped by early Christian liturgy. It explores the contemporary Jewish attribution of the Psalms to David, an idealized figure envisaged as Temple founder and man of prayer. It then shows how this image of David has affected the way the Fourth Evangelist draws on the psalms through quotation, allusion and echo. It frequently demonstrates that the Fourth Gospel attests to Jewish psalm interpretations found in rabbinic sources. Challenging the prevailing view that the Fourth Evangelist intentionally dissociates Jesus from David, this book argues that David as psalmist plays a highly significant role in the Johannine portrayal of Jesus.